Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Loyalitas Pelanggan Provider Telkomsel di Kota Sukabumi - CH Sheni Narulita; Mariati Tirta Wiyata (Institut Manajemen Wiyata Indonesia, 2020)
This study aims to determine the effect of service and product quality on customer loyalty of Telkomsel Provider in Sukabumi City. This type of research is quantitative research. Data through survey technique. The research location is in the city of Sukabumi, West Java. The number of research respondents may be 99 providers of Telkomsel users with a questionnaire. Testing the quality of the instrument (questionnaire) using the validity test and reliability test. The test uses multiple hypothesis analysis, which consists of the T test and F test. The results of this study indicate that the service quality variable (X1) partially does not have a significant effect on the customer loyalty variable (Y) Telkomsel provider, the product quality variable (X2) partially. simultaneous influence on customer loyalty (Y) Telkomsel provider and variables of service quality and product quality simultaneously affect customer loyalty.